Implementasi Program Corporate Social Responsibility Dalam Meningkatkan Citra PT. Khotai Makmur Insan Abadi Tenggarong Seberang - Yunita Evarista (Jurnal Administrasi Bisnis Fisipol Unmul, 2019)
This research aims (i) to find the implementation and form of CSR program which is conducted by PT. Khotai Makmur Insan Abadi and  (ii) to find the impact of implementation CSR towards the image of PT Khotai Makmur Insan Abadi (PT KMIA).This research is a descriptive qualitative research. The determination of this research uses purposive sampling technique. The data collection uses observation, interview, and documentation. The data analysis of this research is using Miles & Huberman’s analysis method. The result of this research shows that CSR PT KMIA indicated by 8 programs Development & Society Empowerment. CSR implementation conducted effectively appropriate with purpose and significance of the CSR program. It is supported by the result of research measured using key performance indicator used by the researcher. Program implementation CSR PT KMIA certainly can creates  the view of society. For the conclusion, implementation CSR PT KMIA has been done optimally, that is to creates a good relation with the society. The suggestion for PT KMIA are to increase their focus on CSR program environmental sector and UKM, in other hand PT KMIA needs to apply financial transparency, and to defend the image of PT KMIA.